Analisis Perlindungan Hukum terhadap Hak Cipta Karya Tulis yang Berjudul Hologramisasi atau Kinegramisasi (Putusan Nomor: 9/Pdt.Sus-Hak Cipta/2020/Pn.Jkt.Pst) - Rahmat Fernando; Anggun Lestari Suryamizon; Jasman Nazar (UNES Law Review, 2023)
Intellectual Property Rights (IPR) are exclusive rights to intellectual property that arise or are born due to human intellectual abilities. From the word intellectual, it is reflected that the source of such wealth is intelligence or the result of human thought which gives birth to intellectual works in the fields of science, art, literature and technology that are beneficial to humans. In connection with the enactment of copyright law protection regulations stipulated in Law Number 28 of 2014 concerning Copyright (hereinafter referred to as the UUHC) with the hope of guaranteeing legal certainty and protection of copyright law itself. In writing this journal, researchers raised several issues, namely legal protection related to the judge's decision on case No. 9/Pdt.Sus-Copyright/2020/PN.Jkt.Pst). This study uses a normative method, which is a process to find legal rules, legal principles, and legal doctrines to answer the legal issues at hand. Normative research does not need to start with a hypothesis, therefore the terms independent variable and dependent variable are unknown in normative research, the data used in this study are primary data, secondary data and tertiary data. This research is based on laws and regulations, books, texts, judge's decisions and journals related to legal protection and legal remedies. Based on the case of researchers regarding violations related to plagiarism of written works committed by a person named Kasim Tarigan and registering the results of plagiarism of his writings at the Directorate General of Intellectual Property (DJKI), where the crime can be subject to civil damages by formal law and material law, as well included in the demands for unlawful acts (PMH). As explained in the provisions of article 1365 of the Civil Code "Any act that violates the law and harms other people requires the person who caused the loss because of his mistake to compensate for the loss".